PEDF and Its Role in Metabolic Disease, Angiogenesis, Cardiovascular Disease, and Diabetes - Crispin R. Dass (Biomedicines, 2025)
This review highlights recent findings on the potent anti-angiogenic serpin protein, pigment epithelium-derived factor (PEDF) as it relates to metabolic disease, diabetes, angiogenesis and cardiovascular disease (CVD), listing a majority of all the publicly available studies reported to date. PEDF is involved in various physiological roles in the body, and when awry, it triggers various disease states clinically. Biomarkers such as insulin, AMP-activated protein kinase alpha (AMPK-α), and peroxisome proliferator-activated receptor gamma (PPAR-γ) are involved in PEDF effects on metabolism. Wnt, insulin receptor substate (IRS), Akt, extracellular signal-regulated kinase (ERK), and mitogen-activated protein kinase (MAPK) are implicated in diabetes effects displayed by PEDF. For CVD, oxidised LDL, Wnt/β-catenin, and reactive oxygen species (ROS) are players intertwined with PEDF activity. The review also presents an outlook on where efforts could be devoted to bring this serpin closer to clinical trials for these diseases and others in general.